IMPROVING THE RHEOLOGICAL AND QUALITATIVE PROPERTIES OF BREAD WHEAT BY BARLEY-EXTRACTED PENTOSANES - Nashmi, R. J.; Naser, J. M. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This study was aimed to improve the rheological and qualitative properties of the most common bread, wheat bread, by barley pentosanes, which is not optimally utilized although it’s many benefits and its huge production. Therefore, water-soluble pentosanes (WSP) and water-insoluble pentosanes (WIP) were extracted from barley (Hordeum vulgare) and added to wheat flour at different percentages. Five treatments were prepared: (T1) from flour only, (T2 and T3) adding WSP at levels(1 and 2%), (T4 and T5) adding WIP at the same levels respectively. The results showed significant improvement in rheological and qualitative properties of the dough and bread made from this dough with increasing the level of addition. The water absorption, the mixing time and the stability time of the dough for T3 and T5, increased from (61.9%) to (64.8 and 65.3%) and from (2min) to ( 2.4 and 3 min) and from (11 min) to (17 and 18 min)respectively, as compared with T1 . Additionally, total scores of sensory evaluation increased from (89.1) to (95.7 and 89.3), the specific volume increased from (4.37 cm3/gm) to (4.79 and 4.54 cm3/gm). The chemical composition analysis showed an increase in the percentages of protein and fat for the same treatments ( T3 & T5 ) as the values increased from (9.34%) to (10.55 and 9.98%) and from (0.85%) to (1.03 and 0.94%) respectively. The percentages of fibre and ash were also increased from (1.71%) to (1.89 and 2.10%) and from (0.74%) to (1.68 and 1.65%) respectively. While the total calorie decreased from (2.73.63 cal) to (261.98 and 253.18 cal).